The Cultural Production of the Educated Person: A Case Study the New Student Admision in Pangkalpinang Bangka - Noblana Adib; Lilik Rofiqoh; Sugeng Riyadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The purpose of this article is to produce new findings or the development of existing theories stating that “the more mature the child the easier it will be for the teacher to teach”. The findings from this research can be used to provide criticism and information for policy, education, and teachers and parents regarding whether children should enter school at the age of 6 and why parents must comply with state regulations on new student admission process (PPDB). The research was conducted in Pangkalpinang, Bangka Belitung Island Province. The researcher observes 4 schools, 7 homeroom teachers of first grade, 4 principles and 235 students of first grade. The technique in collecting data in this article are structured interview and participant observation. This study uses qualitative research method through anthropological approach using ethnography. Finally, the data analysis technique in this article uses reduction, display and verification of data. The article asks whether the culture of school in Bangka Island promote or hinders the principle of the proper age of School. We found that Jean Piaget’s stages of cognitive development have influenced the proper age for school in Bangka Island. The authors believe that Bangka follows the cultural global construction in determining the proper age of a child to enter the elementary school. Keywords: Cultural Production, Student Admission Process, School Age